2001
DOI: 10.1007/bf02234573
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative high-dose radiotherapy on postoperative outcome and colonic anastomotic healing

Abstract: In this rat model, preoperative high-dose radiotherapy using a clinically relevant fractionation scheme does not affect outcome or anastomotic healing when only one limb of the anastomosis is irradiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Firstly, the aim of proximally extended resection is to make sure that the proximal end of anastomosis is non-irradiated. Previous studies have revealed that avoiding the anastomosis of radiated bowel could reduce incidence of anastomotic leak and mortality and achieved good functional results ( 31 34 ). Galland et al reported that for use of non-irradiated bowel for at least one end of an anastomosis, the rate of anastomotic leak decreased from 51.8% (14/27) to 7.1% (1/14) and the mortality decreased from 37% (10/27) to 0 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the aim of proximally extended resection is to make sure that the proximal end of anastomosis is non-irradiated. Previous studies have revealed that avoiding the anastomosis of radiated bowel could reduce incidence of anastomotic leak and mortality and achieved good functional results ( 31 34 ). Galland et al reported that for use of non-irradiated bowel for at least one end of an anastomosis, the rate of anastomotic leak decreased from 51.8% (14/27) to 7.1% (1/14) and the mortality decreased from 37% (10/27) to 0 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, awareness of radiation damage should be raised for anterior resection after nCRT. Several animal studies have revealed that the anastomotic healing is impaired by radiation to both limbs of the bowel anastomosis [32–34]; however, the strength is not affected providing only one-sided limb is irradiated [35, 36]. Clinical evidence also shows that a safe anastomosis in the context of radiation enteritis should be constructed with non-irradiated bowel at least at one end [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative radiotherapy is a significant consideration given its possible association with clinical anastomotic leaks [ 4 ]. When leveraging burst strength or collagen content as an indicator for anastomotic healing, preclinical models are conflicting regarding roles of preoperative radiotherapy, with some suggesting no difference in burst strength [ 115 , 120 ] or similar metrics [ 121 ] while others report a decrease in burst strength with radiotherapy [ 122 , 123 ]. Interestingly, while some suggest that radiotherapy alone is not sufficient to induce anastomotic leak, one study suggests that radiotherapy applied in more highly collagenolytic environments significantly predisposes to leak via enhanced MMP activation [ 121 ].…”
Section: Colorectal Mechanobiologymentioning
confidence: 99%